แนวคิดสำคัญในวารสารสารสุขผู้สูงวัย Themes in the Periodical Wellbeing of the Elderly - เฉยรอด, รัชนีฉาย (Chophayom Journal, 2018)
บทคัดย่อ บทความนี้มีวัตถุประสงค์เพื่อวิเคราะห์แนวคิดสำคัญในวารสารสารสุขผู้สูงวัยโดยใช้ข้อมูลจากวารสารทั้งหมด 8 ฉบับ พบแนวคิดสำคัญ 4 แนวคิด ได้แก่ แนวคิดการเสนอสาระการรีบเร่งวางนโยบายและหามาตรการต่างๆ ของรัฐเพื่อรองรับสังคมผู้สูงอายุ แนวคิดการสนับสนุนให้ผู้สูงอายุดำรงชีวิตอยู่อย่างมั่นคงและมีศักดิ์ศรี แนวคิดการเสริมสร้างสุขภาพอนามัยของผู้สูงอายุ และแนวคิดการส่งเสริมให้ผู้สูงอายุมีหลักประกันรายได้ที่มั่นคงและยั่งยืนทั้งสี่แนวคิดดังกล่าวได้สะท้อนเป้าหมายของวารสารสารสุขผู้สูงวัยที่ผลิตเอกสารข้างต้นเพื่อให้ผู้อ่านกลุ่มผู้สูงอายุมีสุขทั้งกายและใจในฐานะผู้สูงวัยท่ามกลางสภาพสังคมไทยปัจจุบัน คําสําคัญ : แนวคิดสำคัญ, สารสุขผู้สูงวัย, ผู้สูงอายุ ABSTRACT This article aims to analyze the themes that appear in the periodical Wellbeing of the Elderly. From a synopsis of eight issues of the periodical, four major themes were found. These themes related to: proposals for timely policy setting and setting of government measures to accommodate senior citizens; advocating of a secure and dignified lifestyle for the elderly; the strengthening of health and sanitation for the elderly; and the promotion of senior citizens’ guarantee to a secure and sustainable income. These four themes reflect the objectives of the periodical Wellbeing of the Elderly. The issues of the periodical examined in this study were produced with the aim of providing the periodical’s elderly readers with physical and mental wellbeing in their capacity as senior citizens within current Thai society. Keywords : theme, Periodical Wellbeing of the Elderly, senior citizens